THE EFFECT OF BANK RISK RATIO AND EARNING ASSET QUALITY ON PROFITABILITY IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Indrayani, Indrayani; Murhaban, Murhaban; Nurhasanah, Nurhasanah; Zulfikar, Zulfikar; Balqis, Fathia; Irpandi, Wira (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The purpose of this study is to determine the effect of bank risk ratios (represented by credit risk, operational risk and liquidity risk) and the quality of earning assets on profitability in banking companies listed on the Indonesia Stock Exchange for the 2016-2021 period. This study uses data analysis techniques, namely multiple linear regression. The population used in this study were all banking companies listed on the Indonesia Stock Exchange for the 2016-2021 period, the sample used in this study was 15 banks. Based on the results of the analysis conducted, it can be concluded that credit risk represented by Non Performing Loans (NPL) has a significant negative effect on profitability, operational risk represented by Operating Expenses on Operating Income (BOPO) has a significant negative effect on profitability, liquidity risk represented by Loan to deposit Ratio (LDR) has no effect on profitability, and the quality of earning assets has no effect on profitability. Credit risk, operational risk, liquidity risk and earning asset quality significantly affect profitability by 74.4%, while the remaining 25.6% is influenced by factors not included in the research model.